'The palliative care ambulance': A qualitative study of patient and caregiver perspectives of an ambulance service. (June 2023) - Collier, Aileen; Dadich, Ann; Jeffs, Cathie; Noble, Andrew; Crawford, Gregory B
Background: The need for home-based palliative care is accelerating internationally. At the same time, health systems face increased complexity, funding constraints and global shortages in the healthcare workforce. As such, ambulance services are increasingly tasked with providing palliative care. Where paramedics with additional training in palliative care have been integrated into models of care, evaluations have been largely positive. Studies of patient and family carer experiences of paramedic involvement, however, are limited. Aim: To explore patient and family caregiver experiences of paramedics' contribution to palliative care at home. Design: Qualitative interview study. We analysed data within a social constructionist epistemology using reflexive thematic analysis. Setting/participants: Participants receiving specialist palliative care in the community of a metropolitan city of Australia who requested an ambulance between January and August 2018, inclusive. Results: Participants considered paramedics with expertise and experience in palliative care as an extension of the specialist community palliative care team and held them in high regard. Participants highlighted the importance of: critical palliative care at home and a timely, responsive approach; person-centred paramedics; as well as safety and security. Conclusion: Patients and carers feel safe and secure when they know that highly responsive skilled professional support is available when an unexpected problem or sudden change arises, especially out-of-hours, and that support is delivered in an empathic and person-centred manner.